The Effect of Target Passing Training on The Passing Accuracy of Students at The Gajah Mada Soccer School - Herlambang Aditya Nugroho; Imam Hariadi (Journal of Physical and Outdoor Education, 2025)
This study aims to examine the effect of target passing training on the passing accuracy of students at the Gajah Muda Football School (SSB). The research employed a pre-experimental method using a One Group Pretest-Posttest Design. The subjects were 15 students from the U-13 age group at SSB Gajah Muda, selected using total sampling. The instrument used was a soccer passing skill test. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, and the Paired Sample T-Test. The results showed that the data were normally distributed (pre-test: 0.064 > 0.05; post-test: 0.322 > 0.05) and homogeneous (0.511 > 0.05). The Paired Sample T-Test revealed a significant effect of target passing training on passing accuracy (p = 0.000 < 0.05). It can be concluded that target passing training is effective in improving the passing accuracy of students at SSB Gajah Muda